2018
DOI: 10.3855/jidc.10290
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Salmonella spp. in poultry carcasses samples collected in slaughterhouses of Southern Brazil from 2006 to 2015

Abstract: Introduction: This study aimed to evaluate the prevalence of Salmonella on poultry carcasses produced in slaughterhouses of Southern Brazil participating of the Official Pathogen Reduction Program conducted by the Ministry of Agriculture, Livestock, and Supply. Methodology: From 2006 to 2015, 77,165 poultry carcasses were analyzed for presence/absence of Salmonella spp. and the results were statistically evaluated. Results: Prevalence varied from 2.92% to 5.24%, with a mean percentage of 4.04%. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In a world of globalised food production, Salmonella can cross borders through imported food and present a potential risk for public health. Many countries in Europe, including the United Kingdom, import a large amount of poultry from Brazil, which is the largest exporter of chicken meat globally [ 2 , 3 ]. Previous studies have reported the presence of S .…”
Section: Introductionmentioning
confidence: 99%
“…In a world of globalised food production, Salmonella can cross borders through imported food and present a potential risk for public health. Many countries in Europe, including the United Kingdom, import a large amount of poultry from Brazil, which is the largest exporter of chicken meat globally [ 2 , 3 ]. Previous studies have reported the presence of S .…”
Section: Introductionmentioning
confidence: 99%